Perlindungan Hukum Terhadap Tenaga Kerja Borongan Bangunan Atas Keterlambatan Pemberian Upah (Perumahan Tamansari 2) (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2023)
Contract work in construction is one of the common forms of work performed in the construction industry. In contract work, workers are hired to complete construction projects within a specified timeframe and agreed-upon cost. However, there are often cases where contract workers experience delays or wage payment postponements. The research aims to analyze the legal protection for contract workers in the construction industry concerning delayed wage payments. In Indonesia, there are labor regulations that govern the rights and obligations of workers, including wage payments. If there is a delay in wage payment, workers have the right to file a lawsuit or report the violation to the authorities. This research adopts a qualitative research method, analyzing data and gathering information from various sources. Legal protection plays a crucial role in safeguarding workers. Some relevant legal roles include employment agreements, which enable workers to enter into contractual agreements with employers that protect their rights.